First‐Class Health: Amenity Wards, Health Insurance, and Normalizing Health Care Inequalities in Tanzania. (21st April 2014) - Ellison, James
<x xml:space="preserve">Abstract</x> In 2008, a government hospital in southwest Tanzania added a "first‐class ward, " which, unlike existing inpatient wards defined by sex, age, and ailment, would treat patients according to their wealth. A generation ago, Tanzanians viewed health care as a right of citizenship. In the 1980s and 1990s, structural adjustment programs and user fees reduced people's access to biomedical attention. Tanzania currently promotes "amenity" wards and health insurance to increase health care availability, generate revenue from patients and potential patients, and better integrate for‐profit care. In this article, I examine people's discussions of these changes, drawing on ethnographic fieldwork in the 2000s and 1990s. I argue that Tanzanians criticize unequal access to care and health insurance, although the systemic structuring of inequalities is becoming normalized. People transform the language of socialism to frame individualized market‐based care as mutual interdependence and moral necessity, articulating a new biomedical citizenship.